Effect of physical interaction between polyaniline and metal phosphate nanocomposite as positive electrode for supercapattery. (December 2020) - Omar, Fatin Saiha; Numan, Arshid; Bashir, Shahid; Vikneswaran, R.; Ramesh, K.; Ramesh, S.
Highlights: Nanocomposite of PANI/Ni3 (PO4 )2 /Ag3 PO4 as positive electrode of supercapattery. Effect of physical interaction between PANI and metal phosphate. The rate capability of Ni3 (PO4 )2 is significantly enhanced after the addition of Ag3 PO4 and PANI. The supercapattery shows high specific energy and specific power and prolong life cycle. Abstract: The growth of portable technologies and electrical automotive industry has led to the development of supercapattery, as one of the options in the electrochemical energy storage system. In this work, nanocomposite of polyaniline-metal phosphate (comprising nickel phosphate-silver phosphate (Ni3 (PO4 )2 -Ag3 PO4 ) nanocomposite) was synthesized by two-step route; a combination of sonochemical-calcination method, followed by the physical blending method. Structural and morphology studies reveal that crystalline Ag3 PO4 which were decorated on amorphous Ni3 (PO4 )2 were supported by semi-crystalline PANI nanofibers. The electrochemical performance studies show the resultant PANI-Ni3 (PO4 )2 -Ag3 PO4 exhibited significantly improved rate capability from 32% (Ni3 (PO4 )2 ) to 73% with a maximum specific capacity of 677 C/g. The origin of the outstanding performance shown by PANI-Ni3 (PO4 )2 -Ag3 PO4 was due to the synergistic effect produced by the conductive platform provided by PANI, redox behavior of Ni3 (PO4 )2 and extended channels provided by Ag3 PO4 . In order to evaluate the real-time performance of PANI-Ni3 (PO4 )2 -Ag3 PO4, supercapattery devices were fabricated in a configuration of PANI-Ni3 (PO4 )2 -Ag3 PO4 //activated carbon (AC), Ni3 (PO4 )2 -Ag3 PO4 //AC and Ni3 (PO4 )2 //AC. PANI-Ni3 (PO4 )2 -Ag3 PO4 //AC produced a superior performance by providing specific energy of 38.9 Wh/kg at 400 W/kg compared to its counterpart devices. Moreover, the life cycle test of PANI-Ni3 (PO4 )2 -Ag3 PO4 //AC demonstrated high stability which lost only 12% of its initial capacity after 5000 cycles. Graphical abstract: Image, graphical abstract